Melanosis in crustaceans: A review. (January 2016) - Gonçalves, Alex Augusto; de Oliveira, Adriene Rosceli Menezes
Abstract: Melanosis represents a serious problem to the crustaceans industry. Consists on the natural formation of dark pigments mainly in the cephalothorax and joints region, caused by the enzymatic oxidation of phenolic compounds. Despite seeming to be harmless to consumers and not directly associated to microbial spoilage, melanosis affects sensory characteristics reducing products' shelf life and quality. To avoid these issues, several measures are often taken onboard and inside seafood industries, such as different packaging and processing techniques, and most commonly, the use of additives. Worldwide, sulphites are used as the main inhibitors of melanosis; however, are frequently linked to allergic reactions and asthmatic attacks in humans. Therefore, there is increasing interest in a natural alternatives to substitute the chemical compounds used to prevent melanosis. Understanding the processes, causes, and consequences of melanosis is vital to avoid this issue and assure product quality. Therefore, this review aim to ensure faster, simpler access to recent and substantial information on melanosis, where data is concise and easily available. Highlights: To this day, melanosis is still a difficult challenge to the crustacean industry. No techniques are 100% effective in preventing or avoiding melanosis. Organic alternatives to sulfites may be a way to avoid harmful chemical additives.